(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Artificial intelligence technologies improve the learning environment; in the near future, they are expected to provide great benefits for students and teachers, in general, and for those with disabilities and their teachers, in particular. Objective: This research has aimed at identifying the perceptions of special education teachers about the use of artificial intelligence in teaching students with disabilities as well as identifying the impact of some variables, such as the number of years of experience, disability category, or the school stage, on these perceptions. Methods and Participants: The research was based on the descriptive approach. The research sample consists of 301 male and female teachers of students with disabilities from Riyadh, Kingdom of Saudi Arabia. It includes 138 males and 163 females, divided into a group of special education programs. The research used a questionnaire on the perceptions of special education teachers about the use of artificial intelligence in educating students with disabilities. Results: The research findings showed that these teachers’ perceptions were mostly neutral, that there are differences in their perceptions due to the number of years of experience, and that there are no differences in their perceptions due to the disability category or school stage variable. Conclusions: As artificial intelligence is considered one of the modern variables in the field of education for people with disabilities in the Arab environment, it is expected to support personal education, assistive technologies, data-based decision-making when teaching people with disabilities, and promoting inclusion. The research also presented a questionnaire identifying special education teachers’ perceptions of artificial intelligence.